Stereo vision in air force pilots in human centrifuge during +Gz acceleration - Randjelović, Danijela; Šarenac Vulović, Tatjana; Petrović, Nenad; Srećković, Sunčica (Vojnosanitetski pregled, 2021)
Background/Aim. Stereo vision guarantees good vision and is one of the three main elements of binocular vision, besides simultaneous perception and fusion. It represents the third degree of binocular vision and enables estimation of distance, depth, and space between objects, i.e., allows perception of a three-dimensional image, which is crucial for a pilot. The aim of this study was to investigate the effect of +Gz acceleration on stereo vision in pilots in the air force and student pilots. Methods. Two groups of respondents were tested (30 student pilots and 65 air force pilots – a total of 95 respondents). We considered the differences between these two groups as they provide important information about the condition of stereo vision at the beginning of the professional career and after a large number of flight hours over years of flying. We tested variations in stereoscopic vision based on the degree of acceleration of +5Gz by using the Randot Test, which enabled us to determine the degree of three-dimensional vision. Results. Temporary changes in stereo vision in student pilots were greater when compared to these changes in air force pilots when exposed to the same acceleration (+5Gz acceleration). The detailed analysis showed that the most sensitive physiological indicators were changes in stereo vision. Conclusion. We confirmed that individual physiological pilot training in a human centrifuge, where they are exposed to real G acceleration, improves tolerance to accelerations.
Keywords: aerospace medicine; pilots; acceleration; vision tests; space perception; centrifugation